Effectiveness of Team Building Training Improving The Cohesiveness of The Working Group - Wildan Sidiq; Sri Muliati Abdullah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The study aims to test the effect of team building training on the cohesiveness of working groups on production operators on CV. The subject of this study was the employees of production operators who had a low level of cohesiveness. The research method is an experiment with the type